Improving Early Childhood Children’s Ability in Hijaiyah Letters Through PowerPoint-Based Learning Media - Lailatul Qadariyah; Rici Oktari; R Agrosamdhyo; Ahmed Hossam; Wahdiansyah Wahdiansyah (STAI Publisistik Thawalib Jakarta, 2026)
The ability of young children to recognize, pronounce, and write hijaiyah letters remains low due to monotonous and less interactive learning methods. This study aims to assess the effectiveness of PowerPoint-based learning media in improving young children’s skills in recognizing, pronouncing, and writing hijaiyah letters. The research employed a one-group pretest-posttest experimental design. Data were collected through observation and ability tests. Data analysis was performed using SmartPLS to test validity and reliability and to test hypotheses. The results show that students’ mastery of hijaiyah letters is still in the moderate range. Memorization is the weakest aspect, falling into the low category. Post-test scores for students 1–14 ranged only from 1 to 3, indicating no significant improvement compared to the pre-test. Overall, the progress was minimal and not statistically significant. This suggests that learning still needs reinforcement, especially through memorization practice and repetition, to help students recognize, pronounce, and write hijaiyah letters more effectively and evenly. However, interactive PowerPoint media has the potential to enhance children’s learning of hijaiyah letters through engaging, visual, and participatory methods, despite the lack of significant improvement. This study contributes to the development of innovative digital learning tools aimed at improving the quality of hijaiyah letter learning for early childhood education.